Finding value in a heritage landscape: The visitors' perception study - Shuib, K.B; Hashim, H.; Bahrain, N.K. (CRC Press/Balkema, 2015)
There is no doubt that heritage landscape like Bukit Melawati in Kuala Selangor is rich in history and possesses unique character that attracts many local visitors and foreign tourists. However, several literature has highlighted that there is a general public neglect of these valuable heritage due to ignorance which has led to some historical and heritage sites being abandoned or damaged. This paper presents the findings from a study on visitors' perception on Bukit Melawati as a significant heritage tourism destination in the state of Selangor. Some 215 visitors responded to the questionnaire survey carried out at the site. The findings from the study highlighted the tourism potentials and also the perceptions of the visitors about the various monuments, relics and historical remains available at Bukit Melawati. Several suggestions for ensuring a more sustainable tourism of the site are presented at the end of the paper.